2022
DOI: 10.3390/molecules27051495
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Neurotoxic Impacts of Arsenic and the Neuroprotective Effects of Dictyophora Polysaccharide Using SWATH-MS-Based Proteomics

Abstract: Arsenic (As) is one of the most important toxic elements in the natural environment. Currently, although the assessment of the potential health risks of chronic arsenic poisoning has received great attention, the research on the effects of arsenic on the brain is still limited. It has been reported that dictyophora polysaccharide (DIP), a common bioactive natural compound found in dietary plants, could reduce arsenic toxicity. Following behavioral research, comparative proteomics was performed to explore the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…40 Compared with these studies, the present study identified changes in the proteins of complex I in the rat cortex following As exposure and clarified the specific dysregulated protein subunits. In contrast, in our previous study, 26 after As treatment, although mitochondrial-related proteins have changed in the hippocampus of rats, they are not proteins of mitochondrial complexes. This clearly requires further study.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…40 Compared with these studies, the present study identified changes in the proteins of complex I in the rat cortex following As exposure and clarified the specific dysregulated protein subunits. In contrast, in our previous study, 26 after As treatment, although mitochondrial-related proteins have changed in the hippocampus of rats, they are not proteins of mitochondrial complexes. This clearly requires further study.…”
Section: Discussioncontrasting
confidence: 85%
“…60 Similarly, in our previous study, changes in apoptosis-related proteins were observed in the hippocampus of NaAsO 2 -exposed rats. 26 Therefore, NaAsO 2 -induced apoptosis in the brain cells may be related to its neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations